The Role of The Word of Mouth Mediate The Effect of The Marketing Mix on The Decision of Student Parents to Choose Muhammadiyah School: Peran Word of Mouth Memediasi Pengaruh Marketing Mix terhadap Keputusan Orang Tua Siswa Memilih Sekolah Muhammadiyah - Alwifaqi, Jindan; Ambarwati, Rita (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to determine the role of word of mouth in mediating the effect of the marketing mix on the decision of parents of students to choose SMP Muhammadiyah 9 Tanggulangin boarding school, Sidoarjo. This research uses sample data collection through questionnaires. With the number of respondents 125 guardians of SMP Muhammadiyah 9 boarding school Tanggulangin Sidoarjo. For data analysis in this study using statistical techniques Partial Least Square (PLS). The results of this study indicate 2 direct effects are significant, 1 direct effect is not significant. Namely Marketing Mix (X) on parents 'decision to choose school (Y), Marketing Mix (X) on Word of Mouth (Z) and the direct effect that is not significant, namely Word of Mouth (Z) on parents' decision to choose school (Y) . And this study shows that there is an indirect effect that is not significant, namely the Marketing mix on the decision of parents to choose school (Y) through the Word of Mouth (Z).